Agile practices and the promotion of entrepreneurial skills in software development. Issue 9 (22nd February 2018) - Tolfo, Cristiano; Wazlawick, Raul Sidnei; Ferreira, Marcelo Gitirana Gomes; Forcellini, Fernando Antonio
Abstract: This article addresses the relationships between agile development and entrepreneurship. The objective of the study is to verify that the adoption of agile practices can promote entrepreneurial skills in software developers. In this study, agile practices were related to entrepreneurial skills, and developers of the software industry and academia professors were invited to contribute. Questionnaires were sent to the participants to obtain their opinion regarding this research. Participants also opined about the possibility of entrepreneurial skills being an observable behavior in agile culture, ie, if they are visible artifacts of agile culture. As a result, the study found a set of agile practices that promote entrepreneurial skills in software developers. That is, it was found that agile practices promote entrepreneurial behavior in these professionals. These entrepreneurial skills are sustained by the same basic values and assumptions that were learned by developers to resolve internal integration and external adaptation issues during the adoption of agile practices. In this article, an integration model has been adapted from other areas, thereby opening a new field of study involving the relationships between academic research and professional practice on entrepreneurship in the software area and agile development. Abstract : It is shown that agile development practices may foster development of entrepreneurial skills for software developers. Entrepreneurial skills are presented as visible artifacts in agile culture based on the same basic suppositions and values that support agile practice. It proposed a new research area intended to investigate the relationships between practice and academic research in the area of software entrepreneurship and agile development.